Étude Lithostratigraphique Des Formations Superficielles Urbaines Du Secteur Nord De La Ville De Fès, Maroc - Boukhir Mohammed; Jamal Mohamed; Azzouzi Kamal (European Scientific Journal, ESJ, 2017)
The superficial formations of the northern sector of the city of Fez majorly show clay lithostratigraphy in the west of this sector. They are conglomeratic at the center and are composed of limestone deposits in the East. As for the land embankments, they met at two banks of Oued Fès. From a geotechnical point of view, the formations which are exposed to the phenomena of compressing or liquefaction are the argillaceous and anthropic formations. These phenomena of the instability of the grounds can worsen when the water table level increases significantly, especially during the rainy seasons where it can reach the surface at the Oued Fez flood plain. As for the conglomeratic formations, the geotechnical analysis shows that the conglomerates forming a very hard rocky slab constitute a rather solid base and is indeformable. Their thickness, therefore, exceeds 2m of power. This is the case of conglomerates located at the center of this sector. Laboratory tests have classified these soils to be relatively stable.